Raise the quantity in parentheses to the indicated exponent, and simplify the resulting expression. Express answers with positive exponents (-33xy^-1/66x^0y^-3)^2
This is the answer i am getting from TRYING to follow my online book. Please Help Me. Thank You!
I would rethink this. Lets do it in parts:
whole numbers( -33/66)^2= (-1/2)^2= 1/4
x values (x/x^0)^2= x^2
y values (y^-1/Y-3)^2=(y^3-1)^2= y^4
overall: x^2 * y^4 /4
Thanks for your help. I wasn't even using the ^2 outside the parenthesis. Thank YOu!